Xylose–glucose co-fermentation to ethanol by Escherichia coli strain MS04 using single- and two-stage continuous cultures under micro-aerated conditions - Marco T. Fernández-Sandoval; Juvencio Galíndez-Mayer; Francisco Bolívar; Guillermo Gosset; Octavio T. Ramírez; Alfredo Martinez (Microbial Cell Factories, 2019)
Abstract Background Simultaneous co-fermentation of mixed sugars is an important feature to consider in the production of ethanol from lignocellulosic biomass hydrolysates because it enhances the overall ethanol yield and volumetric productivity during fermentation. Continuous cultures can be used during ethanol production from lignocellulosic hydrolysates to prevent catabolite repression by glucose on other sugars, such as xylose, and thus promote the simultaneous and total consumption of sugars and reduce fermentation time. The use of single- and two-stage continuous cultures under micro-aerated conditions for simultaneous consumption of xylose and glucose, and fermentation to ethanol by ethanologenic Escherichia coli strain MS04 was studied. Mineral medium supplemented with glucose, xylose and sodium acetate, was used to compare continuous cultures performance to batch cultures. Results Single-stage continuous cultures under micro-aerated conditions allowed the total co-consumption of a mixture of glucose and xylose (7.5 and 42.5 g/L, respectively) in mineral medium, with steady state ethanol production of 18 g/L, and a volumetric ethanol productivity of 0.9 g/L h, when low dilution rates (0.05 h−1) were used. However, the volumetric productivity was lower than the batch process under similar conditions (1.3 g/L h). Conversely, micro-aerated two-stage continuous culture enhanced the volumetric productivity up to 1.6 g/L h at a dilution rate of 0.15 h−1, with a total consumption of sugars and a slight reduction of the overall ethanol yield. Conclusions The total and simultaneous consumption of glucose and xylose by the ethanologenic E. coli strain MS04 was accomplished by using two-stage continuous culture under micro-aerated conditions with an increase in the volumetric ethanol productivity of 23% and 78% when compared to batch and single-stage continuous cultures, respectively. Multi-stage continuous cultivation can be used to promote the simultaneous consumption of all sugars contained in biomass hydrolysates, and thus increase the volumetric ethanol productivity of the fermentation process.